Up‐regulation of histone methyltransferase SETDB1 by multiple mechanisms in hepatocellular carcinoma promotes cancer metastasis - Wong, Chun‐Ming; Wei, Lai; Law, Cheuk‐Ting; Ho, Daniel Wai‐Hung; Tsang, Felice Ho‐Ching; Au, Sandy Leung‐Kuen; Sze, Karen Man‐Fong; Lee, Joyce Man‐Fong; Wong, Carmen Chak‐Lui; Ng, Irene Oi‐Lin (Hepatology (Baltimore, Md.), 2016)
Epigenetic deregulation plays an important role in liver carcinogenesis. Using transcriptome sequencing, we examined the expression of 591 epigenetic regulators in hepatitis B‐associated human hepatocellular carcinoma (HCC). We found that aberrant expression of epigenetic regulators was a common event in HCC. We further identified SETDB1 (SET domain, bifurcated 1), an H3K9‐specific histone methyltransferase, as the most significantly up‐regulated epigenetic regulator in human HCCs. Up‐regulation of SETDB1 was significantly associated with HCC disease progression, cancer aggressiveness, and poorer prognosis of HCC patients. Functionally, we showed that knockdown of SETDB1 reduced HCC cell proliferation in vitro and suppressed orthotopic tumorigenicity in vivo. Inactivation of SETDB1 also impeded HCC cell migration and abolished lung metastasis in nude mice. Interestingly, SETDB1 protein was consistently up‐regulated in all metastatic foci found in different organs, suggesting that SETDB1 was essential for HCC metastatic progression. Mechanistically, we showed that the frequent up‐regulation of SETDB1 in human HCC was attributed to the recurrent SETDB1 gene copy gain at chromosome 1q21. In addition, hyperactivation of specificity protein 1 transcription factor in HCC enhanced SETDB1 expression at the transcriptional level. Furthermore, we identified miR‐29 as a negative regulator of SETDB1. Down‐regulation of miR‐29 expression in human HCC contributed to SETDB1 up‐regulation by relieving its post‐transcriptional regulation. Conclusion: SETDB1 is an oncogene that is frequently up‐regulated in human HCCs; the multiplicity of SETDB1 activating mechanisms at the chromosomal, transcriptional, and posttranscriptional levels together facilitates SETDB1 up‐regulation in human HCC. (Hepatology 2016;63:474–487)